Wybrane aspekty kapitałowego zaangażowania quasi -funduszy venture capital w Polsce - Świderska, Joanna (Chosen Aspects of Capital Commitment of Venture Capital Quasi-Funds in Poland, 2008)
Venture capital quasi-funds having together about 780 min PLN capital, between 1990 and 2005 made 374 investments, which included financing, in the form of equity and/or debt, firms running a businesses in Poland. The article shows the results of a wider research conducted by the author, concerning chosen aspects of capital commitment of entities mentioned above from the beginning and development of venture capital market in Poland.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 579-587